Not Only the Social Aspects of Creeping Societal Changes - Brychtová Šárka (My University, 2015)
This paper examines possible changes that the society expects in the near future. The changes are mainly in the economic and social spheres of our society. The article in its introductory passages and chapters outlines possible causes of society-wide transformation that it sees largely in the unrestricted application of neoliberal approaches intensified in the last 20-25 years in Europe, which undoubtedly leads to reducing the role of the strong state and a considerable asymmetry of the public and the private sectors, which certainly carries some potential risks. The article, however, attempts to present other ambitions as well - in the context of not only social, but also philosophical and ethical, point out deeper causes of the current much discussed and intractable imbalance.
Sociální a jiné aspekty plíživých společenských změn
Keywords: Economic crisis; Globalization; Public Sector; Concentration of Power; Transformation of Thinking and Society; The causes of crisis; The way from crisis; Balance.; Ekonomická krize; Globalizace; Veřejný sektor; Koncentrace moci; Transformace myšlení a společnosti; Příčiny krize; Cesta z krize; Rovnováha.